The opportunist: The political life of Oswald Pirow, 1915-1959 - Katz, David (Scientia Militaria - South African Journal of Military Studies, 2021)
Finding a mainstream South African publisher for an academic work on South African history is a daunting prospect for an author. Doing so when it involves a niche topic on an obscure personality in a forgotten period of South African history can be even more disheartening. Praise for Protea Book House, who backing Mouton, have provided a mainstream publishing vehicle to bring a fascinating period of our history back into the public domain. Works such as The opportunist: The political Life of Oswald Pirow, 1915–1959 might otherwise have remained inaccessible to the general public, either residing in the rarefied atmosphere of academia or gathering dust on a shelf in a university library as an academic print. The hard truth is that well-researched, peer-reviewed and skilfully written works of history do not necessarily translate into bestsellers, and in most cases, the opposite is true. Publishers with a keen eye on their bottom-line have a set of criteria designed to maximise profit, which often clashes with the lofty standards demanded by academia. For that reason, it is always welcome when a work such as this book by Mouton manages to bridge the academic–popularist divide.